2022
DOI: 10.3389/fnbeh.2021.787383
|View full text |Cite
|
Sign up to set email alerts
|

Disease-Specific Contribution of Pulvinar Dysfunction to Impaired Emotion Recognition in Schizophrenia

Abstract: One important aspect for managing social interactions is the ability to perceive and respond to facial expressions rapidly and accurately. This ability is highly dependent upon intact processing within both cortical and subcortical components of the early visual pathways. Social cognitive deficits, including face emotion recognition (FER) deficits, are characteristic of several neuropsychiatric disorders including schizophrenia (Sz) and autism spectrum disorders (ASD). Here, we investigated potential visual se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 77 publications
(104 reference statements)
2
7
0
Order By: Relevance
“…SzPs have long been noted to have a range of visual processing anomalies ( 29 , 30 , 31 , 32 , 33 ), including in face-emotion recognition ( 34 , 35 ) and the processing of biological motion ( 36 ). These anomalies have been linked to the lateral occipital cortex for visual processing ( 31 , 32 ) and the pSTS for face-emotion recognition ( 17 ). The functional connectivity reductions in this study likely reflect those functional anomalies and may represent disorganization or decreased/impaired use of this cortical region ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SzPs have long been noted to have a range of visual processing anomalies ( 29 , 30 , 31 , 32 , 33 ), including in face-emotion recognition ( 34 , 35 ) and the processing of biological motion ( 36 ). These anomalies have been linked to the lateral occipital cortex for visual processing ( 31 , 32 ) and the pSTS for face-emotion recognition ( 17 ). The functional connectivity reductions in this study likely reflect those functional anomalies and may represent disorganization or decreased/impaired use of this cortical region ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Social perception areas were defined as regions of interest (ROIs) derived from three localizer tasks: 1) a task that contrasted activity evoked by moving versus static facial expressions, designed to localize areas involved in face-emotion recognition ( 17 ); 2) a visual search task designed to activate areas involved in visual processing, visual attention, and cognitive control ( 12 , 18 , 19 ); and 3) a task designed to activate areas involved in ToM operations evoked during the viewing of a short animated video ( 20 ). Based on the localizers and prior studies, the resulting 98 areas were then subdivided into 28 component systems.…”
Section: Methodsmentioning
confidence: 99%
“…In Sz, studies have reported reduced MNS activation during action observation (Mehta et al 2014;Valizadeh et al 2022), in association with impaired TOM performance (Choe et al 2018) and negative symptom severity (Schilbach et al 2016). In recent studies (Martinez et al 2018;Martinez et al 2019;Martínez et al 2022), we have observed reduced MT+ activation in Sz in response to simple motion stimuli which correlate with reduced FER to static emotional faces (Martinez et al 2018), suggesting a potential involvement of MT+ deficits even to static-only stimuli. In this study, we investigated the parallel cortical circuitry underlying the perception of real-and implied-motion in individuals with Sz.…”
Section: Introductionmentioning
confidence: 62%
“…Functional magnetic resonance imaging (fMRI) studies have shown that MT+ activation is reduced in Sz in response to simple moving stimuli, in parallel with elevated motion-detection thresholds and reduced motioninduced event-related potentials (ERP) (Chen et al 2008;Lencer et al 2005;Martinez et al 2018;Martinez et al 2019). Additionally, MT+ activation deficits in Sz are associated with aberrant interactions involving V1 and PulN (Martinez et al 2018;Martínez et al 2022). The sensitivity of MT+ is not limited to real physical motion but extends also to the representation of implied-motion derived from static images containing cues conveying information about an objects' motion direction and speed (Fawcett et al 2007;Kourtzi and Kanwisher 2000;Osaka et al 2010;Senior et al 2000;Zeki et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Viewers make a forced choice of lie vs. sarcasm after each trial. In other neuropsychiatric disorders, deficits in early visual processing contribute to impairments in social cognition [ 25 , 36 , 48 ], leading us to investigate a potential similar relationship with Aβ deposition.…”
Section: Methodsmentioning
confidence: 99%